Design and Synthesis of an Inositol Phosphate Analog Based on Computational Docking Studies - Peng, Zhenghong (2013)
A virtual library of 54 inositol analog mimics of In(1,4,5)P(3) has been docked, scored, and ranked within the binding site of human inositol 1,4,5-trisphosphate 3-kinase A (IP(3)-3KA). Chemical synthesis of the best scoring structure that also met distance criteria for 3′-OH to -P in Phosphate has been attempted along with the synthesis of (1S,2R,3S,4S)-3-fluoro-2,4-dihydroxycyclohexanecarboxylic acid as an inositol analog, useful for non-invasive visualization and quantitation of IP(3)-3KA enzymatic activity